2008
DOI: 10.1007/s10637-008-9188-2
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin reduces human melanoma cell migration by down-regulating αVβ3 integrin and reducing metalloproteinase 2 production

Abstract: Artemisinin and its derivatives are well known antimalarial drugs, particularly useful after resistance to traditional antimalarial pharmaceuticals has started to occur in Plasmodium falciparum. In recent years, anticancer activity of artemisinin has been reported both in vitro and in vivo. Artemisinin has inhibitory effects on cancer cell growth and anti-angiogenetic activity. In the present investigation, we analyzed the inhibitory effects of artemisinin on migratory ability of melanoma cell lines (A375P and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…Our data show that DHA inhibits ovarian cancer via reducing the proliferation and adhesion of ovarian epithelial cancer cells in vitro. These data are consistent with other findings that DHA is able to inhibit the proliferation of several other malignant cell lines (3)(4)(5)(6)(7)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data show that DHA inhibits ovarian cancer via reducing the proliferation and adhesion of ovarian epithelial cancer cells in vitro. These data are consistent with other findings that DHA is able to inhibit the proliferation of several other malignant cell lines (3)(4)(5)(6)(7)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 93%
“…Our study demonstrated that DHA inhibit production of MMP-2 only, suggesting that DHA may differentially regulate MMPs and inhibit ovarian cancer metastasis via the MMP-2 pathway. Our data are consistent with the previous observation that inhibition of cell migration by artemisinin (an analogue of DHA) was associated with decreased expression of MMP-2 (22). On the other hand, MMP-9 is highly up-regulated in ovarian cancer, particularly in metastases (19).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There are reports that inhibition of carcinoma cell adhesion using various chemotherapeutic agents plays an important role in cancer treatment (Efferth et al, 2001;Huang et al, 2007;Buommino et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified several potential mechanisms by which the artemisinins can act against cancer cells. They have been shown to be antiproliferative through action on key cell cycle regulatory proteins such as p21 waf1cip1 and cyclin D1 [20]; pro-apoptotic by manipulating the Bax:Bcl-2 rheostat [21,22]; antiangiogenic by targeting vascular endothelial growth factor [23,24]; and anti-migratory through their effects on αVβ3 integrins [25]. The multi-modal character of these antimalarial drugs, allied to their low host toxicity even at high doses [26,27], reinforces the priority for them to be developed as a novel anti-cancer agents.…”
Section: Artemisinin (Art) Is a Natural Trioxane That Is Isolated Fromentioning
confidence: 99%